Augmented Optical Retention and Improved Antibacterial Activity against Conjunctivitis of Moxifloxacin Hydrochloride Entrapped in Microsponges in situ Gel: Formulation Evaluation and in vivo Remedial Value in Rabbits - Sharma, Sangeet Kumar; Kumar, Ishab; Rohilla, Ankur; Khatri, Ramchander; Hooda, Tanuj; Rohilla, Seema (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives: Moxifloxacin hydrochloride is an antibiotic related to flouroquinolones class. It possessed reasonable to exceptional efficacy against gram-negative ocular pathogens. The prime goal of this study was to formulate and estimate moxifloxacin hydrochloride entrapped microsponge in situ gel to treat conjunctivitis. Materials and Methods: Moxifloxacin hydrochloride loaded microsponges was manufactured using modified emulsion-solvent dispersion technique. Optimized microsponge group was integrated into Carbopol base after in vitro characterization to formulate 1% moxifloxacin hydrochloride entrapped microsponge gel. Then, the prepared gel was examined for ocular irritancy, isotonicity, sterility testing, antimicrobial activity. Drug deposition ability and in vivo efficacy of above optimized batch was compared with marketed preparation in rabbit eye with conjunctivitis. Results: The mean particle size and ex vivo release of drug from optimized microsponge formulation was depicted to be 4.83±0.26 |jm and 75.80±1.5 at the ending of 24 hr and entrapment was found to be 85.51±0.74%. SEM study evidenced the porous, spherical morphology of microsponges whereasFT-IR confirmed the microsponges’ formation. No irritation in eye was observed with moxifloxacin hydrochloride microsponge in animals. Conclusion: It was concluded that moxifloxacin hydrochloride entrapped microsponge have shown augmented penetration of drug and in situ gel enhance the exposure time of drug loaded microsponges and conjunctiva of eye. Thus, moxifloxacin hydrochloride encapsulated microsponge gel can be investigated further as a medication to cure conjunctivitis.
Keywords: Microsponges; Moxifloxacin hydrochloride; Occular; Conjunctiva; Emulsion